Habituation-Based Character Education in Islamic Primary Schools: Integrating the 7 Habits Framework within the Merdeka Curriculum - Halimatus Sa’diya; Avidatul Umaidah; Isnainiyah; Subianto; Muhammad Hasan; Ahmad Fauzi (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
Despite widespread adoption of character education programs in Indonesian Islamic primary schools, a persistent gap remains in understanding how global character frameworks can be systematically integrated with local religious curricula to produce holistic student development. While habituation-based approaches have shown promise for fostering discipline and religiosity, existing studies predominantly describe isolated practices without examining the conceptual mechanisms that enable sustainable integration between daily routines and formal religious instruction. This study addresses this lacuna by investigating the implementation of the